(untitled) (Slavic Studies, 2025)
The paper investigates phraseological units in the field of chromatic colours in Slovenian and Croatian. The analysis includes Slovenian and Croatian phrasemes and proverbs containing one of the five chromatic colours that can be traced as components of phraseological units in both languages, namely red, blue, green, yellow and pink. On the basis of the affinities and historical contacts between the two languages, we have assumed that the phraseological units and the meanings with which these colours appear in them are mostly similar in the two languages.